Detection of Mycobacterium avium subsp. paratuberculosis in a sheep flock in Tuscany - Galiero, Alessia; Fratini, Filippo; Turchi, Barbara; Colombani, Giuseppe; Nuvoloni, Roberta; Cerri, Domenico (Tropical animal health and production, 2015)
Paratuberculosis is an infectious disease which affects ruminants. In this work, a sheep flock in Garfagnana district (Tuscany, Italy) was examined by agar gel immune-diffusion (AGID) tests, culture, and PCR from feces, milk, tissue samples, and cheeses. At the first AGID test, 7/280 (2.5 %) animals were positive. From these animals, feces and milk samples were collected: 4/7 feces (57.14 %) and 2/7 milk samples (28.57 %) were positive to culture and 7/7 (100 %) feces samples and 1/7 milk samples (14.28 %) were positive to PCR; 2/4 (50 %) cheeses ripened for 14 days and 1/3 (33.33 %) cheese ripened for 20 days were positive to PCR, from which no viable microorganisms were isolated. Then, the AGID-positive animals were slaughtered and tissue samples were taken from one sheep with PCR-positive feces and milk: the liver, intestine, mesenteric lymph nodes, but not the spleen and mammary lymph nodes were positive to culture; all these samples were instead PCR-positive. After 1 year, a second AGID survey was performed on the remaining animals: 6/244 (2.45 %) subjects were positive to this test. Data obtained revealed the presence of paratuberculosis in a sheep population in Garfagnana.